Pharmacogenomics: a perspective of personalized medicine in CHD treatment as a model - PRANCULIS, Aidas; KUČINSKIENĖ, Zita Aušrelė; KUČINSKAS, Vaidutis (Acta medica Lituanica, 2011)
Although several drug dosage algorithms are available, clinicians today still commonly use the trial and error method in discovering what medicine and in what doses will be most beneficial for each patient. There are currently still very few tools available to help solve these problems, although nowadays there is more and more evidence to show that for a number of drugs, genetic variability plays an important (and sometimes central) role in variable response to drugs.This review is focused on the variation within the genes associated with the function of medicines from major pharmaceutical groups of drugs used for the treatment of coronary heart disease (CHD). These include anticoagulants, β-blockers, angiotensin-converting enzyme (ACE) inhibitors, antiarrhythmics, angiotensin II receptor lockers (ARBs), diuretics, and statins. The progress in the field of CHD pharmacogenomics, which is one of the major focuses in the field of cardiovascular medicine, is ensured by a multitude of studies generating some statistically significant findings that will quite plausibly change the way clinicians treat patients on an individual level.Pharmacogenomic research of cardiovascular medicine in the majority of cases has provided conflicting results thus delaying the implementation of genetic testing to create genotype-based medication dosing algorithms. Nevertheless, analysis of the literature reveals that based on the pharmacogenomic research progress of warfarin and to some extent clopidogrel, the practical use of pharmacogenomics in the future is plausible.Keywords: pharmacogenomics, coronary heart disease, medications